2022
DOI: 10.1096/fasebj.2022.36.s1.r2065
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Aloe‐derived natural products as lead scaffolds for SARS‐CoV‐2 main protease (Mpro) inhibitors

Abstract: In the past two years, the COVID‐19 pandemic has caused over 5 million deaths and 250 million infections worldwide. Despite successful vaccination efforts and emergency approval of small molecule therapies, diverse antivirals are still needed to combat the inevitable viral resistance that will arise. The main protease of SARS‐CoV‐2 (Mpro) is an attractive drug target due to the clinical success of protease inhibitors against other viruses, such as HIV and HCV. However, in order to combat resistance, diverse ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Further studies suggested that compound 382 was a reversible SARS‐CoV‐2 3CL pro inhibitor, while compound 415 might form a covalent bond with Cys145 of 3CL pro 232 . Similarly, aloesin was identified as a SARS‐CoV‐2 3CL pro inhibitor from a fluorescence resonance energy transfer (FRET)‐based THS assessment 233 …”
Section: Naturally Derived Sars‐cov‐2 3clpro Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies suggested that compound 382 was a reversible SARS‐CoV‐2 3CL pro inhibitor, while compound 415 might form a covalent bond with Cys145 of 3CL pro 232 . Similarly, aloesin was identified as a SARS‐CoV‐2 3CL pro inhibitor from a fluorescence resonance energy transfer (FRET)‐based THS assessment 233 …”
Section: Naturally Derived Sars‐cov‐2 3clpro Inhibitorsmentioning
confidence: 99%
“…232 Similarly, aloesin was identified as a SARS-CoV-2 3CL pro inhibitor from a fluorescence resonance energy transfer (FRET)-based THS assessment. 233…”
Section: Quinones and Their Derivativesmentioning
confidence: 99%
“…Anacardic acid is the main component of extracts from Ginkgo biloba and Rhus verniciflua , which has a wide range of pharmacological activities such as antibacterial, anticancer, and antiviral ( Hundt et al, 2015 ; Park et al, 2018 ; Saedtler et al, 2020 ). Recent studies have confirmed that the EC 50 value of antiviral activity of anacardic acid is 9 μM in live SARS-CoV-2 virus by targeting Mpro ( Chen et al, 2021b ; Hicks et al, 2022 ; Li et al, 2022 ; Xiong et al, 2021 ; Yan et al, 2022b ). Our study demonstrated that anacardic acid is likely a novel competitive inhibitor targeting both PLpro and Mpro of SARS-CoV-2, and more in vivo experiments for its antiviral mechanism will be explored in the future.…”
Section: Discussionmentioning
confidence: 93%